2020
DOI: 10.1016/j.scitotenv.2020.140775
|View full text |Cite
|
Sign up to set email alerts
|

An efficient Chlorella sp.-Cupriavidus necator microcosm for phenol degradation and its cooperation mechanism

Abstract: A Chlorella sp.-Cupriavidus necator (C. necator) consortium was artificially established for phenol degradation. The synergistic relationship between Chlorella sp. and C. necator was initially demonstrated, and then the effects of Chlorella sp./C. necator inoculation ratio, light intensity, temperature and pH on the performance of this consortium were systematically evaluated and optimized. The optimal conditions for phenol degradation were as follows: a Chlorella sp./C. necator inoculation ratio of 1:1, a lig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…Many reports have been demonstrated that co-culture of microalgae and bacteria enhanced the phenol degradation and improved the biomass of microalgae. Yi et al (2020) reported that Chlorella sp. monoculture could not degrade 400 mg L −1 phenol, and its growth was seriously inhibited.…”
Section: Introductionmentioning
confidence: 99%
“…Many reports have been demonstrated that co-culture of microalgae and bacteria enhanced the phenol degradation and improved the biomass of microalgae. Yi et al (2020) reported that Chlorella sp. monoculture could not degrade 400 mg L −1 phenol, and its growth was seriously inhibited.…”
Section: Introductionmentioning
confidence: 99%